Testing the water: Understanding stakeholder readiness for strategic coastal and marine management. (February 2015) - Mason, Claire M.; Lim-Camacho, Lilly; Scheepers, Kelly; Parr, Joanna M.
Abstract: We argue that stakeholder commitment and cooperation is essential for the success of strategic coastal and marine management initiatives and draw upon social identity theory to explain how inter-group relationships can either support or hinder cooperation across stakeholder groups. We analyse data from interviews carried out with 24 coastal and marine stakeholders from the Northern Territory, Australia, looking at how stakeholders describe their objectives for coastal and marine management and evidence of social identity effects either facilitating or impeding cooperation between stakeholders. While most participants sought improvements to coastal and marine management, only some were thinking in terms of a more regional-scale, forward-looking and integrated approach. Strong social identity effects inhibiting cooperation between stakeholders were evident in many of the interviews. However, the interviews also revealed shared objectives (e.g., the need for more data, to avoid duplication of effort, and more transparent and systematic decision-making) that could serve as a basis for developing a common social identity, and fostering the commitment and cooperation needed for strategic coastal and marine management initiatives. Highlights: Strategic coastal and marine management needs stakeholder cooperation and commitment. Relationships between stakeholder groups can either facilitate or impede cooperation. Stakeholder objectives and social identity effects were analysed from interview data. Most participants were not seeking a truly integrated approach to marine management. Shared objectives were identified that could be used to build cooperation and commitment.